Prevalence of vitamin D deficiency in Africa: a systematic review and meta-analysis - Reagan M Mogire, MSc; Agnes Mutua, BSc; Wandia Kimita, MSc; Alice Kamau, MSc; Philip Bejon, PhD; John M Pettifor, MBBCh; Adebowale Adeyemo, MD; Thomas N Williams, FMedSci; Sarah H Atkinson, PhD (Elsevier, 2020)
Summary: Background: Vitamin D deficiency is associated with non-communicable and infectious diseases, but the vitamin D status of African populations is not well characterised. We aimed to estimate the prevalence of vitamin D deficiency in children and adults living in Africa. Methods: For this systematic review and meta-analysis, we searched PubMed, Web of Science, Embase, African Journals Online, and African Index Medicus for studies on vitamin D prevalence, published from database inception to Aug 6, 2019, without language restrictions. We included all studies with measured serum 25-hydroxyvitamin D (25[OH]D) concentrations from healthy participants residing in Africa. We excluded case reports and case series, studies that measured 25(OH)D only after a clinical intervention, and studies with only a meeting abstract or unpublished material available. We used a standardised data extraction form to collect information from eligible studies; if the required information was not available in the published report, we requested raw data from the authors. We did a random-effects meta-analysis to obtain the pooled prevalence of vitamin D deficiency in African populations, with use of established cutoffs and mean 25(OH)D concentrations. We stratified meta-analyses by participant age group, geographical region, and residence in rural or urban areas. The study is registered with PROSPERO, number CRD42018112030. Findings: Our search identified 1692 studies, of which 129 studies with 21 474 participants from 23 African countries were included in the systematic review and 119 studies were included in the meta-analyses. The pooled prevalence of low vitamin D status was 18·46% (95% CI 10·66-27·78) with a cutoff of serum 25(OH)D concentration less than 30 nmol/L; 34·22% (26·22-43·68) for a cutoff of less than 50 nmol/L; and 59·54% (51·32-67·50) for a cutoff of less than 75 nmol/L. The overall mean 25(OH)D concentration was 67·78 nmol/L (95% CI 64·50-71·06). There was no evidence of publication bias, although heterogeneity was high (I2 ranged from 98·26% to 99·82%). Mean serum 25(OH)D concentrations were lower in populations living in northern African countries or South Africa compared with sub-Saharan Africa, in urban areas compared with rural areas, in women compared with men, and in newborn babies compared with their mothers. Interpretation: The prevalence of vitamin D deficiency is high in African populations. Public health strategies in Africa should include efforts to prevent, detect, and treat vitamin D deficiency, especially in newborn babies, women, and urban populations. Funding: Wellcome Trust and the DELTAS Africa Initiative.